اسلام میں خدمت خلق کے طریقے اورمعاصرتطبیقی عوامل کا تضمینی مطالعہ: A Comprehensive Study of Methods for Serving Humanity in Islam and Their Contemporary Applications - Hira Zaman; Palwasha Jalil; Khushhall Shaheen (Al Manhal Research Journal, 2024)
The societal system in Islam is based on brotherhood, love, tolerance, and mutual cooperation and service, which does not accept the existence of mutual animosity and class conflict. It is a principle introduced by Islam that, when adhered to, eliminates class struggle and feelings of vengeance between the rich and the poor, leading humanity towards genuine peace and tranquility. In any society, the presence of mutual cooperation and service strengthens its foundation, while on the other hand, diseases of self-interest and selfishness can cause it to collapse instantly. Islam has closed all those paths that lead society to disharmony and become a source of disruption. Life progresses peacefully and towards development through the triangle of the individual, family, and society. As time progresses, there are requirements for the improvement of society, and only by fulfilling these requirements can society move forward and provide facilities to its inhabitants. However, if the fundamental principles of the individual, family, and society are not maintained, that society will become a bastion of ignorance and a well of stagnant thoughts. For this reason, Islam has laid down principles to create a better society. Among these are various methods of serving humanity, including financial service, physical service, and spiritual service. These discussions will be elaborated upon in the following lines.